Allergen immunotherapy - Salman, Türker (Nova Science Publishers, Inc., 2024)
Due to some limitations of allergen avoidance and drug therapy, which are the first methods used to improve the clinical picture of allergy, researchers are directed to new treatment options. Allergen immunotherapy (AIT) involves the repeated administration of specific allergen extracts to patients with increasing doses over 3-5 years. A successful AIT stimulates long-term clinical tolerance to allergens, either completely eliminates or reduces the severity of symptoms, minimizes the need for medication, and thus improves the quality of life of patients with a genetic predisposition to allergies. Various routes of administration such as oral, sublingual, epicutaneous, intralymphatic, and intranasal have been added to subcutaneous immunotherapy, which has been applied for nearly a century. These new ways of application, which are tried to increase the compliance of the patients with the treatment, shorten the treatment period, and reduce the health costs, draw attention both in terms of clinical and scientific research. © 2024 Nova Science Publishers, Inc. All rights reserved.
Keywords: Allergen immunotherapy; Allergy; Subcutaneous allergen immunotherapy; Sublingual allergen immunotherapy